2000
DOI: 10.1161/01.res.86.5.571
|View full text |Cite
|
Sign up to set email alerts
|

Atrial but Not Ventricular Fibrosis in Mice Expressing a Mutant Transforming Growth Factor-β 1 Transgene in the Heart

Abstract: Increased transforming growth factor (TGF)-beta(1) activity has been observed during pathologic cardiac remodeling in a variety of animal models. In an effort to establish a causal role of TGF-beta(1) in this process, transgenic mice with elevated levels of active myocardial TGF-beta(1) were generated. The cardiac-restricted alpha-myosin heavy chain promoter was used to target expression of a mutant TGF-beta(1) cDNA harboring a cysteine-to-serine substitution at amino acid residue 33. This alteration blocks co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
217
1
4

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(230 citation statements)
references
References 28 publications
8
217
1
4
Order By: Relevance
“…We conclude that our library is an initial approximation of the in situ expression pattern of fibroblasts in the intact mouse heart. 9 The generated cardiac fibroblast SAGE library comprises the major part of the transcriptome of these cells. The relatively high number of unique transcripts per cell obtained with the SAGE technology (30,507 unique transcripts in the present study) in comparison with estimates of 10,000 -15,000 different transcripts per average cell has been a matter of debate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We conclude that our library is an initial approximation of the in situ expression pattern of fibroblasts in the intact mouse heart. 9 The generated cardiac fibroblast SAGE library comprises the major part of the transcriptome of these cells. The relatively high number of unique transcripts per cell obtained with the SAGE technology (30,507 unique transcripts in the present study) in comparison with estimates of 10,000 -15,000 different transcripts per average cell has been a matter of debate.…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin-I increased proliferation and collagen synthesis in skin fibroblasts, whereas it inhibited these in cardiac fibroblasts [3]. Important molecular factors shown to mediate phenotypic changes in cardiac fibroblasts in response to injury are angiotensin II [4][5][6][7], transforming growth factor β [8,9], norepinephrine [10] and endothelin-1 [11]. Cardiac myocytes also secrete atrial and brain natriuretic peptides (ANP, BNP) which have potent systemic activities such as natriuresis, diuresis and vasodilation.…”
Section: Introductionmentioning
confidence: 99%
“…2,23 Although the present study clearly showed an important role of TGF-␤, it is possible that other factors are involved in the mechanisms of myocardial fibrosis and diastolic dysfunction. Recently, Nakajima et al 25 reported that transgenic mice overexpressing a constitutively active TGF-␤ 1 mutant show atrial but not ventricular fibrosis, although active TGF-␤ levels are similar in the atria and ventricles. Currently, the reason for the conflicting results regarding the role of TGF-␤ in ventricular fibrosis is unknown, although the discrepancy may be caused by differences between the animal models used in our and their studies.…”
Section: Limitationsmentioning
confidence: 99%
“…The increased left ventricular dilatation suggests no change in collagen synthesis but probably changes in the post-translational modification or collagen cross-linking, which might result in weaker scar formation (Cleutjens et al, unpublished results). The moderate effect of TGF-β inhibition on the left ventricle might be explained by the findings of Nakajima et al [98], who found that cardiac specific overexpression of TGF-β in mice resulted in elevated fibrosis in the atria but not in the ventricles. In contrast, TGF-β inhibition in a model of cardiac pressure overload hypertrophy in rats resulted in prevention of myocardial fibrosis, and reversed diastolic dysfunction [99].…”
Section: Indirect Interventions In Collagen Metabolismmentioning
confidence: 99%